Assessment of Knowledge on Side Effects Among Cancer Patients Receiving Radiotherapy in Selected Hospitals of West Bengal - Sukanya Chowdhury; Chayan Paul (RGUHS Journal of Nursing Sciences)
Background and Aim Approximately 20 million new cases of cancer and 9.7 million cancer deaths will occur in 2022. Lung cancer is the most frequently diagnosed type of cancer. Radiotherapy is an integral part of cancer management and is associated with several adverse effects. Awareness of the general population is still poor in both developing and developed countries. Therefore knowledge assessment of patients with cancer is necessary to understand the lack of knowledge regarding cancer.Objectives This descriptive study aimed to assess the knowledge of the side effects of cancer patients receiving radiotherapy in selected hospitals in West Bengal.Method A total of 171 samples were selected using a non-probability purposive sampling technique and a validated structured interview schedule was used to collect data from the study samples.Results The study results showed that the mean and SD of knowledge score were 11.3 and plusmn3.06 respectively 25.1 of cancer patients had a poor level of knowledge and the majority of the study sample had side effects such as nausea fatigue weight loss and psychological changes. There was a significant association between the knowledge of cancer patients and sex educational status place of residence family history of cancer and duration of radiotherapy Plt0.001. This study has implications for nursing practice education administration and research.Conclusion The majority of the patients had a poor level of knowledge. Further studies with larger participants and different populations are required to understand the knowledge and awareness.